2024
DOI: 10.1177/20531680231225316
|View full text |Cite
|
Sign up to set email alerts
|

Null effects of social media ads on voter registration: Three digital field experiments

Asli Unan,
Peter John,
Florian Foos
et al.

Abstract: Civic organisations and progressive campaigns regard digital advertising as an essential method to register to vote low-participation groups, such as ethnic minorities, young voters and frequent home movers like private-sector tenants. Digital strategies appear to be promising in countries like the UK, where the registration process can be completed online, usually in less than 5 minutes, using a web link in the advert. But are typical digital campaigns effective in registering voters? To find out, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…By recognizing emails as an important form of political communication, we also highlight that a political campaign's communication goals may be multi-faceted. Of course, many studies examining the effect of social media (e.g., Bail et al, 2020;Campbell, 2013;Enikolopov et al, 2020;Fujiwara et al, 2023;González-Bailón et al, 2023;Guess et al, 2023bGuess et al, , 2023aHaenschen, 2016;Nyhan et al, 2023;Theocharis & Lowe, 2016) and digital advertising (e.g., Aggarwal et al, 2023;Beknazar-Yuzbashev & Stalinski, 2022;Bond et al, 2012;Liberini et al, 2023;Unan et al, 2024) on politics have focused on changes in political attitudes or voting-related behaviors. However, these very technologies can also be used to achieve other political campaign goals, including (though not limited to) fundraising (Auter & Fine, 2018;Petrova et al, 2021).…”
Section: Why Studying Emails Is Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…By recognizing emails as an important form of political communication, we also highlight that a political campaign's communication goals may be multi-faceted. Of course, many studies examining the effect of social media (e.g., Bail et al, 2020;Campbell, 2013;Enikolopov et al, 2020;Fujiwara et al, 2023;González-Bailón et al, 2023;Guess et al, 2023bGuess et al, , 2023aHaenschen, 2016;Nyhan et al, 2023;Theocharis & Lowe, 2016) and digital advertising (e.g., Aggarwal et al, 2023;Beknazar-Yuzbashev & Stalinski, 2022;Bond et al, 2012;Liberini et al, 2023;Unan et al, 2024) on politics have focused on changes in political attitudes or voting-related behaviors. However, these very technologies can also be used to achieve other political campaign goals, including (though not limited to) fundraising (Auter & Fine, 2018;Petrova et al, 2021).…”
Section: Why Studying Emails Is Importantmentioning
confidence: 99%
“…Some studies have provided evidence for the effects of political advertising on increasing voters' political knowledge (e.g., Atkin et al, 1973;Surlin & Gordon, 1977), affecting candidate image evaluation (e.g., Atkin & Heald, 1976;Becker & Doolittle, 1975), and impacting voters' election decisions (e.g., Kaid & Sanders, 1978;Weaver-Lariscy & Tinkham, 1996). However, when it comes to voter turnout, recent studies have found minimal effects of political advertising (e.g., Aggarwal et al, 2023;Beknazar-Yuzbashev & Stalinski, 2022;Unan et al, 2024).…”
Section: Emails For Political Advertisingmentioning
confidence: 99%